Trends and features of digital transformation development in the media of Kazakhstan - Shindalieva, М.Б.; Zhanysbayeva, А.П.; Tulebaуeva, С.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
Abstract. XXI century-the era of Information Society and technological modernization. At this stage, the concept of digital transformation was not limited to economic or technical areas, but became the main driving force for socio-communicative systems as well. In particular, journalism is one of the areas that are most deeply influenced by digital technologies. Today, the processes of production, distribution and perception of information have radically changed, and traditional forms of journalism have been replaced by new media formats. From this point of view, the scientific analysis of the impact of digital transformation on journalism is an urgent problem of high theoretical and practical importance. Digital technologies not only automated media production and increased the speed of news distribution, but also changed the professional role of a journalist. A modern journalist is not just a provider of information, he is a creator of multimedia content, an interactive link with the audience, and an ethical moderator of the digital space. Therefore, the relevance of the study is to comprehensively reveal the impact of new technologies on professional standards, ethics and public relations in journalism. The main goal of the search is to identify the impact of digital transformation on development trends in modern journalism, professional standards and the formation of new media formats. Here we will analyze the theoretical foundations of the concept of digital transformation, the peculiarities of new technologies and content formats in the field of journalism (online, multimedia, mobile, podcasting and data journalism), about the change in journalistic ethics and professional standards in the digital age. One of the main tasks of the study is to provide forecasts regarding the development of digital journalism in the Kazakh media space and the development of future journalism. The object of the study was the processes of digital journalism in modern Kazakhstan and world practice. The subject of the study is the impact of digital technologies on journalistic content, ethics and professional standards. The article used methods of analysis, comparison, content analysis, Control, and synthesis. The author explains the main directions of transformation in journalism in theoretical and practical terms, analyzing specific examples in the media sphere (Kazakhstan internet publications, podcast platforms, multimedia projects). As a result of the study, it is proved that digital transformation radically changes the trajectory of the development of journalism. Information speed, interactivity and Multimedia narrative approaches have become the main indicators of the professional competence of a modern journalist. At the same time, ethical responsibility, fact-checking and maintaining a trusting relationship with the audience remain the main mission of journalism in the digital age. In practical terms, this study is suitable for use as an additional educational material in the teaching of the disciplines "New Media", "Multimedia Journalism", "Media Ethics" at the faculties of journalism.